Development of Functional Chicken Chips using Flaxseed and Oats Powder - Kasthuri, S.; Mandal, P.K.; Pal , U.K. (Journal of Meat Science, 2016)
Consumption of unhealthy snack foods with high fat content, added chemical preservatives and low nutritive value is one of the predisposing factors for most of the lifestyle diseases. So, there is need for development of ready-to eat shelf stable functional meat chips. This study was undertaken to standardize the recipe and procedure for preparation of chicken chips. Chicken chips recipe and procedure were standardized and three cooking methods viz. deep fat frying, microwave cooking and hot air oven cooking were compared. Sensory scores for appearance, flavour, texture, crispiness and acceptability were significantly (p
Keywords: Functional chicken chips; Flaxseed powder; Oats powder; Sensory quality